Implementation of fuzzy PID controller on hot air blower system / Atiqah Liyana Md Said, Norlela Ishak and Mazidah Tajjudin - Md Said, Atiqah Liyana; Ishak, Norlela; Tajjudin, Mazidah (UiTM Press, 2022)
This paper focuses on the modeling, development, and implementation of a Fuzzy PID controller in controlling the heating system. This study will look into the effectiveness of a fuzzy Proportional Integral Derivative (PID) control scheme for this application. Instead of using a trial-and-error method for the controller tuning, this study proposes a fuzzy PID control to tune the controller parameters and to improve the conventional PID controller transient response. Modeling of the PT326 heating system is required before designing the controller. Through the MATLAB System Identification Toolbox, a discrete-time model is obtained and represented by an ARX model structure. A simulation study had been implemented on a unit step input. The results demonstrated that the system shows positive improvement in terms of rise time and settling time when fuzzy PID controller was applied.